To fully expand and simplify the given expression, we need to multiply each term in the first expression by each term in the second expression:
First, distribute -7𝑦^5 in the second expression:
-7𝑦^5 * 3𝑦^9 = -21𝑦^14
-7𝑦^5 * 3𝑦 = -21𝑦^6
-7𝑦^5 * 5 = -35𝑦^5
Next, distribute 5 in the second expression:
5 * 3𝑦^9 = 15𝑦^9
5 * 3𝑦 = 15𝑦
5 * 5 = 25
Now, combine all the terms:
-21𝑦^14 + 15𝑦^9 - 21𝑦^6 - 35𝑦^5 + 15𝑦 + 25
Therefore, the fully expanded and simplified expression is:
-21𝑦^14 + 15𝑦^9 - 21𝑦^6 - 35𝑦^5 + 15𝑦 + 25
Fully expand and simplify: ( − 7 𝑦^5 + 5 ) ( 3 𝑦^9 + 3 𝑦 + 5 )
1 answer